AMORPHOUS STRUCTURE IN CU-ZN-V-AL OXIDE COMPOSITE CATALYST FOR METHANOL REFORMING - Mahmud, Mohd Sabri; Yaakob, Zahira; Mohamad, Abu Bakar; Wan Daud, Wan Ramli; Dai Viet, Vo Nguyen (IIUM Engineering Journal, 2018)
Cu-Zn-V-Al oxide composite catalysts were prepared using a co-precipitation method to investigate hydrogen and carbon monoxide yield of a methanol reforming reaction. The mass compositions of metals were initially determined on the Simplex Centroid statistical design. The effects of various metal compositions on the physicochemical properties of the catalyst were studied via X-ray diffractogram (XRD), temperature-programmed reduction (TPR) analyses, and reaction. XRD revealed crystals in the samples. Crystalline CuO in Cu30V30Al40 formed with the addition of zinc oxide at the metal loading below 30 wt%. A combination of zinc oxide and vanadia, however, had no Zn-V complex crystal but its scanning electron microscopy image showed the formation of string structures (AS). The catalyst that contained the AS exhibited a broad hydrogen reduction peak in the TPR analysis. Vanadium at a loading below 40 wt% with various zinc and cuprum compositions also formed small ASs and exhibited single TPR peaks. A reaction yield study revealed the optimum compositions of metal oxides when the data was fitted by response surface plots. The catalysts with high content of AS were not at the peaks however. Cu-Zn based catalysts showed the highest hydrogen yield for the reaction temperature of between 150 oC to 225 oC and vanadia-promoted catalyst with AS only appeared to be the optimum catalyst at the higher temperature. ABSTRAK: Mangkin komposit oksida Cu-Zn-V-Al disediakan menggunakan kaedah pemendakan bersama untuk mengkaji hasil hidrogen dan karbon monoksida daripada tindak balas pembentukan semula metanol. Komposisi jisim logam-logam dikenal pasti terlebih dahulu menggunakan reka bentuk statistik Simplex Centroid. Pelbagai kesan komposisi logam terhadap sifat-sifat mangkin kimia-fizikal dikaji menerusi analisis-analisis pembelauan sinar-X (XRD) dan program penurunan suhu teratur (TPR), dan tindak balas kimia. Hasil analisis XRD menzahirkan kristal pada sampel-sampel. Hablur CuO terbentuk dalam Cu30V30Al40 dengan penambahan zink oksida pada muatan logam kurang daripada 30% berat. Gabungan zink oksida dan vanadia walau bagaimanapun tidak menghasilkan hablur kompleks Zn-V, namun imbasan imej mikroskop elektron menunjukkan pembentukan struktur tetali (AS). Mangkin yang mengandungi AS menunjukkan penurunan puncak hidrogen yang lebar dalam analisis TPR. Vanadium pada muatan berat logam kurang daripada 40% berbanding komposisi zink dan kuprum juga membentuk AS kecil dan menghasilkan puncak-puncak TPR tunggal. Hasil tindak balas kajian menunjukkan komposisi optimum oksida logam apabila data ujikaji dipadankan dengan menggunakan plot permukaan respon. Mangkin yang mempunyai kandungan AS tertinggi bagaimanapun tidak berada pada puncak. Mangkin berasaskan Cu-Zn menunjukkan hasil hidrogen tertinggi bagi suhu tindak balas antara 150 oC hingga 225 oC dan mangkin yang ditambah vanadia bersama AS pula muncul sebagai mangkin optimum pada suhu lebih tinggi.